Oil Price Fluctuation and their Impact on the Macroeconomic Variables: The Case of Kuwait - Alawadhi, Salah A.; Longe, Adedayo E. (International Journal of Energy Economics and Policy, 2024)
The fluctuations in the international prices of crude oil have been a major concern for many economies who depend mainly on oil exports. Oil price shocks are a major disturbance for the economies of oil producing countries. This study investigates the impact of oil price shocks on selected macroeconomic variables in Kuwait using secondary data covering the period of 2001 to 2022. The study adopted the Vector autoregression (VAR) method to analyze the response of Kuwait macroeconomic variables to shocks in oil prices. Oil price in the study is considered in 2 categories: the linear oil price and the non-linear oil price (positive and negative changes in oil price). Based on the findings, it is observed that oil price shocks significantly impact macroeconomic variables in Kuwait. It is found that positive changes in oil prices have a more positive and significant impact on the macroeconomic variables compared to the negative changes in oil price. It is however concluded that there is a need for more policy developments to better harness periods of positive oil price experiences, and develop hedging risk framework for periods of negative changes in oil price in order to curb the impact of oil price shocks on Kuwait’s macroeconomy.